Penaksiran Suhu Ruangan Pada Termometer dengan Menggunakan Inverse Regression - Hesty Fadilah; Helma Helma (Journal of Mathematics UNP, 2020)
Abstract— Temperature measurements using a thermometer sometimes produce higher or lower output than that actual value. This research aims to determine the suitability of the thermometer with the conditioned room temperature to find out the predicted temperature value from the thermometer measurement. In this case the room temperature is conditioned according to the need and then the temperature is measured using a thermometer simultaneously. A total of 40 measurement data were then analyzed statistically using the inverse regression method. Based on the results of the study it can be seen that the suitability of the thermometer  to the conditioned room temperature (  with a confidence level of 95%. Keywords—Thermometer, Actual Value, Output Value, Inverse Regression.